TRANSFORMASI PROSPEK KERJA LULUSAN PENDIDIKAN DASAR MELALUI EDUPRENEURSHIP DI TENGAH REFORMASI TENAGA PENDIDIK - Alya Nadiastuti; Bagas Muktinasrowi (CV. Denasya Smart Publisher, 2026)
The world of work in the education sector has undergone significant changes due to teacher reform and the development of digital technology. The policy of structuring honorary workers and the ASN-based and PPPK-based teacher recruitment system has increased job competition for elementary education graduates. These conditions have encouraged education graduates to adapt and seek alternative career development outside the formal teaching profession. This study aims to analyze the transformation of job prospects for elementary education graduates towards edupreneurship amidst the teacher reform. The study used a literature review method by reviewing various scientific journals, books, and relevant documents published between 2018 and 2025. Data were collected through academic source searches and analyzed using qualitative descriptive techniques. The results show that the development of digital technology opens new opportunities for elementary education graduates to develop careers based on educational entrepreneurship, such as developing digital learning media, online tutors, educational content creators, and digital platform-based educational businesses. In addition, digital literacy, creativity, communication, and entrepreneurial skills are important competencies in facing the changing world of education. This study concludes that edupreneurship can be a strategic alternative for career development that is relevant for elementary education graduates in addressing the limitations of formal employment opportunities and supporting economic independence in the digital era.